If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(4y + -5) = 3y + 5y Reorder the terms: 8(-5 + 4y) = 3y + 5y (-5 * 8 + 4y * 8) = 3y + 5y (-40 + 32y) = 3y + 5y Combine like terms: 3y + 5y = 8y -40 + 32y = 8y Solving -40 + 32y = 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. -40 + 32y + -8y = 8y + -8y Combine like terms: 32y + -8y = 24y -40 + 24y = 8y + -8y Combine like terms: 8y + -8y = 0 -40 + 24y = 0 Add '40' to each side of the equation. -40 + 40 + 24y = 0 + 40 Combine like terms: -40 + 40 = 0 0 + 24y = 0 + 40 24y = 0 + 40 Combine like terms: 0 + 40 = 40 24y = 40 Divide each side by '24'. y = 1.666666667 Simplifying y = 1.666666667
| [-6+(-13)]+8=-6+(m+8) | | 11-4p=-5(p-1) | | -8a-2(2a-1)=-40+2a | | 3.2+0.17-w=5.75 | | 5v+18=2(8v-2) | | 92+2x=78+3x | | 86=32+6(x-2) | | 25+2m=5(m+2) | | -10+r=-7(6+r) | | 8y-16=13y-9 | | -6+4(1+8x)=-194 | | 188=-4(1+6b) | | 7-6(-5b-5)=157 | | 9-2(-5x+8)ifx=-9 | | 7-66(-5b-5)=157 | | -6+5x=9 | | X-9=3.5 | | -3(6k-5)=123 | | f(x)=3-2(1) | | -4(-7n+8)=-228 | | b^2+11b=-30 | | 4x-x=-5+8x | | x^2=-99 | | -4r+5=10-5r | | -7b-2b=8-8b | | 9=3x-6 | | f(x)=3-2(0) | | 6+3x-x=x+2 | | X-7325=4561 | | 19.2+(-7+3.8)= | | 150=3x | | 3(2(13)+(-4))= |